Quantitative Measures of Craniofacial Dysmorphology in a Family Study of Schizophrenia and Bipolar Illness. (20th March 2015) - Deutsch, Curtis K.; Levy, Deborah L.; Price, Selya F. R.; Bodkin, J. Alexander; Boling, Lenore; Coleman, Michael J.; Johnson, Fred; Lerbinger, Jan; Matthysse, Steven; Holzman, Philip S.
Abstract : Several laboratories, including ours, have reported an overrepresentation of craniofacial (CF) anomalies in schizophrenia (SZ). How might this dysmorphology arise in a brain-based disorder? Because the brain and face derive from shared embryologic primordia and morphogenetic forces, maldevelopmental processes may result in both CF and brain dysmorphology. Our approach is 2-pronged. First, we have employed, for the first time in the study of psychiatric disorders, objective measures of CF morphology that utilize an extensive normative database, permitting computation of standardized scores for each subject. Second, we have rendered these findings biologically interpretable by adopting principles of embryology in the analysis of dysmorphology. Dependent measures in this investigation focused on derivatives of specific embryonic primordia and were contrasted among probands with psychotic disorders, their first-degree relatives, and normal controls (NC). Subject groups included patients with a diagnosis of SZ ( N = 39) or bipolar (BP) disorder with psychotic features ( N = 32), their clinically unaffected relatives ( N = 82 and N = 41, respectively), and NC ( N = 95) subjects. Anomalies involving derivatives of frontonasal and mandibular embryonic primordia showed a clear association with psychotic illness, as well as familial aggregation in relatives in both diagnostic groups. In contrast, one class of CF anomalies emerged only among SZ probands and their first-degree relatives: dysmorphology arising along the junction of the frontonasal and maxillary prominence derivatives, manifested as marked asymmetries. This class was not overrepresented among the BP patients nor among their relatives, indicating that this dysmorphology appears to be specific to SZ and not a generalized feature of psychosis. We discuss these findings in light of embryologic models that relate brain regions to specific CF areas.